1993
DOI: 10.1590/s0101-81751993000200007
|View full text |Cite
|
Sign up to set email alerts
|

Contribuição à herpetologia da Argentina e do Rio Grande do Sul, Brasil por William Wright Milstead (Amphibia, Reptilia)

Abstract: ABSTRACf. CONTRJBUTION TO TI-IE I-IERPETOLOGY OF ARGEN-TINA ANO RJO GRANDE DO SUL, BRAZIL BY WILLIAM WRJGI-IT MILSTEAD (AMPI-IIBIA, REPTILIA). ln lhis pape r wC are presenting lhe list or lhe specimens and the laxa oblained; lhere are 73 names of species bel onging to 40 genera, of which 32 species and B genera are amphibians, and 42 species and 27 genera are repliles. There are several field nOles of Milstead and manydala on lhe snakes studied by Lema with Milstead. The collection was widespread by Milstead t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Almeida and Cardoso (1985) did not question the presence of a sperm with double tail, though they commented that the flagella moved like a single element. These ideas were also followed explicitly or implicitly (by employing Hyla instead of Ololygon) by Peixoto (1982, 1984), Haddad et al (1988Haddad et al ( , 1990, Cardoso and Martins (1987), Haddad and Sazima (1992), Langone (1991), Andrade andCardoso (1987, 1991), Abe and Neto (1991), Langone and Prigioni (1988), Klappenbach and Langone (1992), de Lema and Braun (1993), Taboga and Dolder (1993), Rossa-Feres and Jim (1994), and Martins (1998). noticed that some species of Ololygon (based on representatives of the then O. catharinae, O. staufferi, and O. rubra species groups) had the ability to bend their thumbs and first toes backward and suggested that this could be a synapomorphy of the genus.…”
Section: Historical Background: a Brief History Of Scinaxmentioning
confidence: 99%
“…Almeida and Cardoso (1985) did not question the presence of a sperm with double tail, though they commented that the flagella moved like a single element. These ideas were also followed explicitly or implicitly (by employing Hyla instead of Ololygon) by Peixoto (1982, 1984), Haddad et al (1988Haddad et al ( , 1990, Cardoso and Martins (1987), Haddad and Sazima (1992), Langone (1991), Andrade andCardoso (1987, 1991), Abe and Neto (1991), Langone and Prigioni (1988), Klappenbach and Langone (1992), de Lema and Braun (1993), Taboga and Dolder (1993), Rossa-Feres and Jim (1994), and Martins (1998). noticed that some species of Ololygon (based on representatives of the then O. catharinae, O. staufferi, and O. rubra species groups) had the ability to bend their thumbs and first toes backward and suggested that this could be a synapomorphy of the genus.…”
Section: Historical Background: a Brief History Of Scinaxmentioning
confidence: 99%
“…The authors seemed to suggest that the degree of morphological variation between both groups is equivalent to that among other species groups of Hyla, and presumably because of this, placing the two groups in a single genus is not justified. These ideas were also followed explicitly or implicitly (by employing Hyla instead of Ololygon) by Peixoto (1982, 1984), Haddad et al (1988Haddad et al ( , 1990, Cardoso and Martins (1987), Haddad and Sazima (1992), Langone (1991), Andrade andCardoso (1987, 1991), Abe and Neto (1991), Langone and Prigioni (1988), Klappenbach and Langone (1992), de Lema and Braun (1993), Taboga and Dolder (1993), Rossa-Feres and Jim (1994), and Martins (1998). Almeida and Cardoso (1985) did not question the presence of a sperm with double tail, though they commented that the flagella moved like a single element.…”
Section: Historical Background: a Brief History Of Scinaxmentioning
confidence: 99%